1998
DOI: 10.1016/s0029-7844(98)00143-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for preeclampsia in nulliparous women in distinct ethnic groups: a prospective cohort study

Abstract: In studies of risk factors for preeclampsia, black women should be analyzed separately from white women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
73
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 15 publications
7
73
3
Order By: Relevance
“…[4][5][6] In our study we found Cape Verdean women but not Surinamese-Creole and Antillean women to have a higher risk of preeclampsia. This is in contrast to the study of Knuist et al, 6 who found SurinameseCreole, Antillean, and West-African women to have a higher risk of preeclampsia. Previously, we have shown that DBP is more strongly associated with the risk of gestational hypertensive disorders and might be a better predictor of gestational hypertensive disorders than SBP.…”
Section: Ethnicity Blood Pressure and Gestational Hypertensive Disocontrasting
confidence: 42%
See 4 more Smart Citations
“…[4][5][6] In our study we found Cape Verdean women but not Surinamese-Creole and Antillean women to have a higher risk of preeclampsia. This is in contrast to the study of Knuist et al, 6 who found SurinameseCreole, Antillean, and West-African women to have a higher risk of preeclampsia. Previously, we have shown that DBP is more strongly associated with the risk of gestational hypertensive disorders and might be a better predictor of gestational hypertensive disorders than SBP.…”
Section: Ethnicity Blood Pressure and Gestational Hypertensive Disocontrasting
confidence: 42%
“…In line with our study, another Dutch study among 2413 pregnant women found Dutch women to have the highest SBP levels in pregnancy and the lowest DBP levels for Mediterranean women. 6 This may suggest blood pressure differences to reverse during pregnancy and to be higher among white women compared with other ethnic groups. One possible explanation might be that the maternal cardiovascular system of the various ethnic groups adapts differently during pregnancy because of genetic differences or different environmental factors.…”
Section: Ethnicity Blood Pressure and Gestational Hypertensive Disomentioning
confidence: 99%
See 3 more Smart Citations